Inflation Uncertainty and Relative Price Variability in WAEMU Countries - Gerling, Kerstin; Fernandez Valdovinos, Carlos (Washington, D.C. : International Monetary Fund, 2011)
Using a consistent dataset and methodology for all eight member countries of the West African Economic and Monetary Union (WAEMU) from 1994 to 2009, this paper provides evidence of the two major channels for real effects of inflation: inflation uncertainty and relative price variability. In line with theory and most evidence for advanced and emerging market economies, higher inflation increases inflation uncertainty and relative price variability in all WAEMU countries. However, the pattern, magnitude and timing of these two channels vary considerably by country. The findings raise several policy issues for future research.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet